Vaccination in Niger : Issues of perception, governance and response to the COVID-19 pandemic. - (:unkn) unknown (My University, 2025)
This booklet is the result of in-depth research conducted as part of the Alliance SHS Africa project between 2023 and 2025, aimed at exploring the social, political, and cultural dynamics surrounding vaccination in several African countries, including Niger. It brings together empirical data collected in the field, interviews with institutional and community stakeholders, and a multidisciplinary analysis combining contributions from sociology, anthropology, public health, and political science.The COVID-19 pandemic has highlighted both the limitations and the potential of health systems in Africa. It has revealed the tensions between global public health approaches and local realities, between biomedical medicine and indigenous knowledge, and between institutional communication and informal information networks. Niger, a Sahelian country marked by significant logistical constraints and disparities in access to healthcare, provides a unique perspective on vaccine governance and the forms of support or resistance expressed within it.This booklet is intended for a wide audience: researchers, healthcare professionals, policymakers, students, and, more broadly, anyone interested in public health issues in the Global South. It offers a reading grounded in field realities, attentive to the voices of local populations, and committed to contributing to concrete improvements in health policies.
Keywords: African Research